Penggunaan Insektisida Komersial dalam Pengendalian Vektor Demam Berdarah Dengue di Provinsi Riau - Hubullah Fuadzy; Firda Yanuar (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2018)
Commercial insecticide generally used by the people to reduce Aedes spp. mosquito infestation. The practice of using one type of insecticide for long period may induce the risk of mosquito tolerance. The purpose of this study is to analyse the habits of people using commercial insecticides for controlling Aedes spp. infestation in Riau Province. The source of data in this study was obtained from the research of